2011
DOI: 10.1530/joe-11-0154
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence of retinoid X receptor in the green crab Carcinus maenas: a possible role in female reproduction

Abstract: Retinoid X receptor (RXR) belongs to an ancient superfamily of nuclear hormone receptors, and plays an important role in reproduction of vertebrates. However, the reproductive role of RXR has not been clarified in crustaceans. In this investigation, we first report the cloning of two alternative splice variants of RXR cDNA from green crab ovarian RNA. RXR mRNA levels were quantified in different vitellogenic stages of the crab hepatopancreas (HP) and ovary. The expression of RXR mRNA relative to the arginine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 47 publications
(65 reference statements)
3
40
0
Order By: Relevance
“…Similarly, the injection of EcR-dsRNA into white leg shrimp Litopenaeus vannamei decreased the expression of ecdysteroid signaling response genes (Qian et al 2014). It has also been reported that in the shore crab C. maenas, the in vitro Rxr-dsRNA treatment of ovarian tissue led to significantly inhibited expression of both Rxr and Vg (Nagaraju et al 2011). In this study, the results of silencing experiments clearly indicated that the addition of EcR-dsRNA to the ovarian explants downregulated the expression of both SpEcR and SpVg, which occurred even when exogenous 20E was concurrently added.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, the injection of EcR-dsRNA into white leg shrimp Litopenaeus vannamei decreased the expression of ecdysteroid signaling response genes (Qian et al 2014). It has also been reported that in the shore crab C. maenas, the in vitro Rxr-dsRNA treatment of ovarian tissue led to significantly inhibited expression of both Rxr and Vg (Nagaraju et al 2011). In this study, the results of silencing experiments clearly indicated that the addition of EcR-dsRNA to the ovarian explants downregulated the expression of both SpEcR and SpVg, which occurred even when exogenous 20E was concurrently added.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to the more common N-terminal domain RXR isoforms observed in insects and vertebrates, atypical isoforms arising through differential splicing in the RXR hinge and LBD domain have been identified in several brachyuran crabs (Chung et al, 1998a;Durica et al, 2002;Kim et al, 2005;Nagaraju et al, 2011;Techa and Chung, 2013), and in the hinge domain of the prawn, Marsupenaeus japonicus (Asazuma et al, 2007). In U. pugilator, sequencing studies and ribonuclease protection assays (RPA) have shown the existence of two regions of variability in UpRXR protein, differing in the inclusion or omission of a five amino acid sequence in the hinge region, and a 33 amino acid sequence in the LBD domain.…”
Section: Introductionmentioning
confidence: 99%
“…The RAR isolated from the crab has been found to bear a close similarity to vertebrate RARs in the ligand-binding domain. To date, RXR was identified from the ovaries of C. pugilator, G. lateralis, M. japonicas, F. chinensis, C. maenas, Scylla serrata and Daphnia magna [32][33][34][35][36][37][38]. Recently, RXR has been also identified in the eyestalks of Callinectes sapidus [39] O. senex [40] and M. nipponence [41].…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, RXR has been also identified in the eyestalks of Callinectes sapidus [39] O. senex [40] and M. nipponence [41]. Reduction in mRNA levels for RXR and for vitellogenin in the crab, C. maenas after treatment with RXR dsRNA [36] and fluctuations in expression of RXR mRNA in ovaries during reproduction [30] suggests RA acts as reproductive hormone. RAs in crustaceans are also identified as morphogens involved in the limb bud regeneration and morphogenesis [13,14].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation